Negritude, francofonia e cultura africana Léopold Sédar Senghor como paradigma - Riesz, János (2020)
The article tries to define the relations and tensions between "Négritude", Francophonie" and "African Culture" based on the person of L Senghor. L.S. incarnated and represented all three positions successively and simultaneously; his reflection as a poet and as a statesman can be defined by his effort to surpass the gag between the antagonisms and contradictions of the three positions. A historical look at this attempt shows us clearly the limits of such an "accord conciliant". Success and failure by L. Senghor and "his" century can be read both as a task and as a utopia for generations to come.